The Use of Semantic Translation Method in á¸Œauâ€™u al-MisbÄh fÄ« BayÄni AhkÄmi al-NikÄh - Fitriah, Nauval; Hidayatullah, Moch. Syarif (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2020)
This study was aimed at investigating the use of semantic translation method in the translation of the á¸Œauâ€™u al-MisbÄh fÄ« BayÄni AhkÄmi al-NikÄh by K.H. Hasyim Asy'ari. A descriptive qualitative method was used in this study. After translating the data objects, the analysis process was carried out by describing the use of semantic translation method applied to translate the text. The results of this study revealed that semantic translation method used in translating á¸Œauâ€™u al-MisbÄh fÄ« BayÄni AhkÄmi al-NikÄh was an effective method to use in translating such classical texts, in which it eases the translator to produce translations that are acceptable in the target language (TL), easy to understand, and as closely as possible with the meaning of the sourch language (SL), and help the translator to preserve the writer's ideas.